Pancangan Galam pada Pondasi di Tanah Rawa Banjarmasin - Nursyarif Agusniansyah; Gusti Novi Sarbini (Arsir: Jurnal Arsitektur, 2024)
Galam piles are used as foundations in swampy soils in Banjarmasin, especially in house building. The condition of the swampy soil with different water levels affects the galam piling process. Knowledge of this requires a method in its implementation. This research aims to formulate an identification’s method of galam piling in Banjarmasin's swampy soil on various land conditions. Its revealing implementation details, techniques, applications after the galam piling work is carried out. By describing the implementation of galam piling in Banjarmasin's swampy land along with the use of materials, tools, alternative systems/constructions and other variations. It will describe the relationship between the theory of galam piling and the actual implementation process from field data, coupled with a detailed description of the implementation experience. Method in this research was, field observation studies, will be conducted at various construction sites in Banjarmasin, especially the object of building houses and low-rise buildings of 2 (two) floors. The result of the research is the implementation method of galam piling which is an applicative description that occurs in the field with conditions on Banjarmasin swamp land. The benefit of this research is as a guide for field implementers in carrying out galam piling on swamp soil foundations. There are details that must be considered in relation to the application of theory and implementation methods.